Penguatan Peran Polri dalam Menanggulangi Intoleransi dan Radikalisme Guna Mencegah Terorisme Tahun 2023 - Saputra, Azis; Dadang Sutrasno; Widi Setiawan (Pusat Penelitian dan Pengembangan Polri, 2024)
Indonesia as a pluralistic country pays quite extensive attention to religious life based on Pancasila and as a religious nation state, namely a national state that protects and facilitates all the religions of its citizens. Indonesia has laws and regulations that encourage tolerant life, guaranteeing the rights of religious freedom. , prohibit hate speech and to tackle terrorism. However, since the reform era until now, religious harmony and freedom have often been disrupted by the actions of intolerant and radical groups who understand religious differences incorrectly. Therefore, the National Police Research and Development Center conducted research on Strengthening the Role of the National Police in Tackling Intolerance and Radicalism to Prevent Terrorism. The aim of this research is to explain and analyze the challenges and efforts of the National Police as well as the role of society in overcoming intolerance and radicalism. This research uses qualitative and quantitative methods. Respondents consisted of the public and Police personnel. The research results stated: 1)The situation of inter-religious harmony shows a relatively conducive situation; 2)In most areas, dealing with intolerance, radicalism and terrorism has not become a priority, either for Police or for community leaders and local governments; 3)The most prominent and frequently encountered cases of intolerance in the research location (community) are: rejection houses/places of worship, rejection of certain religious activities/rituals and religious blasphemy; 4)The potential radicalism by ex-convicts who have not returned to the Republic of Indonesia is also still a problem in itself; 5)In general, community participation in preventing intolerance and radicalism can be seen from two aspects, namely cultural and structural; 6)So far, only police stations that have ex-convicts in their area have received a budget for training/mobilizing ex-convicts.